Continental Celtic Word Formation The Onomastic Data - GARCÍA ALONSO, Juan Luis (Aquilafuente, 2014)
The book you have in your hands has its distant ancestor in an International Symposium held at the University of Salamanca in September 2011 (2nd-4th) and entitled «Continental Celtic Word Formation. The Onomastic Data». The idea for this gathering arose from a series of conversations between Juan Luis García Alonso, Patrick Sims-Williams and Alexander Falileyev in Aberystwyth in March 2010. This book is undoubtedly indebted to this previous event (belonging in a series that we might call our «Ptolemy Workshops», held in Aberystwyth in 1999 (Ptolemy: Towards a linguistic atlas of the earliest Celtic place-names of Europe, edited by David Parsons and Patrick SimsWilliams, Aberystwyth, 2000), Innsbruck in 2000, Madrid in 2002 (New Approaches to Celtic Place Names in Ptolemys Geography, edited by Javier de Hoz, Eugenio Luján and Patrick Sims-Williams, Madrid, 2005), Munich in 2004, and Salamanca in 2006 (Celtic and Other Languages in Ancient Europe, edited by Juan Luis García Alonso, Salamanca, 2008). In any case, this book is an ulterior development of what was discussed in the 2011 Salamanca gathering. The new approach this time, as can be clearly appreciated from the title chosen, consisted in a specific look at the word formation of proper names in order to both gain a more accurate idea of how Celtic proper names are formed and furnish ourselves with further tools to identify a specifically doubtful name as Celtic beyond the tricky and slippery path of etymological analysis.